1991
DOI: 10.1055/s-2008-1045987
|View full text |Cite
|
Sign up to set email alerts
|

Die Verwendung von autologem Ohrknorpel in der Lidchirurgie

Abstract: Autologous ear cartilage is relatively easy to procure in suitable form and sufficient quantity. At the donor site, there are, as a rule, no complications to be expected. Autologous ear cartilage without conjunctival coverage is of good use for replacing and lengthening the inner layer of an eyelid, not only to reconstruct large eyelid-defects, but also to give additional support and length. The cartilage graft will grow on well, provided the wound is well vascularized. This must not be expected with scarring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…All eyelid layers must be repaired, guaranteeing stability as well as mobility in order to maintain the corneal lubrication and cleansing, in addition to providing blinking, especially with regard to the upper eyelid [22,29]. Cartilage grafts have usually been used in segmental or total loss to achieve such goals [12,21,24,25,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All eyelid layers must be repaired, guaranteeing stability as well as mobility in order to maintain the corneal lubrication and cleansing, in addition to providing blinking, especially with regard to the upper eyelid [22,29]. Cartilage grafts have usually been used in segmental or total loss to achieve such goals [12,21,24,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical access to the concha is simple and morbidity is low, unfortunately the concha is relatively thick. In the 90's, Heinz used a silastic lamina to separate the conchal cartilage graft from the bulbar conjunctiva, and reported good results [12,18]. However, Matsuo in 1987 [20,21], reported the possibility of using the conchal cartilage graft with the perichondrium placed directly in contact with the bulbar conjunctiva and showed that cover with conjunctiva from the edges of the defect occurred in 3 to 4 weeks.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation